Important role of alloyed polymer acceptor for high efficiency and stable large-area organic photovoltaics. (July 2022) - Park, Sungmin; Park, So Hyun; Jin, Hyunjung; Yoon, Seongwon; Ahn, Hyungju; Shin, Seoeun; Kwak, Kyungwon; Nah, Sanghee; Shin, Eul-Yong; Noh, Jun Hong; Min, Byoung Koun; Son, Hae Jung
Abstract: We developed high performance PM6:N3 bulk-heterojunctions by synthesizing polymers as the second acceptor. The acceptor PY-P2 where a biphenyl linker makes the polymer chain to have high dihedral angles forms intricate alloy-like composites in N3 domains whereas stiff polymer chain of PY-T2 exists separated from the acceptor domain. Introduction of PY-P2 results in much longer lifetimes and diffusion lengths of excitons generated in N3 domain of the PM6:N3:PY-P2 blend compared to those of the excitons in PM6:N3 as well as PM6:N3:PY-T2. Consequently, the PM6:N3:PY-P2 based OPV devices show improved exciton dissociation and change transport with reduced charge recombination. The PM6:N3:PY-P2 organic photovoltaic (OPV) devices prepared with blade-coating at 1 cm 2 active area achieved efficiency of 15.2% compared with 12.9% of the PM6:N3 control device; whereas, the corresponding OPV device using PY-T2 shows decreased efficiency of 11.7%. OPV mini-module (active area 5.4 cm 2 ) with PY-P2 achieves high efficiency of 14.7% compared with 11.9% of the PM6:N3 devices. Furthermore, the alloyed PY-P2 acceptor effectively improves OPV thermal stability under 85 °C heating for 1000 h, compared with PY-T2 and control devices. We demonstrated importance of the second polymer acceptor for achieving high-performance large-area OPV, which is significantly affected by its chemical structure. Graphical Abstract: We developed high performance PM6:N3 bulk-heterojunctions by introducing the second acceptor PY-P2. This results in longer lifetimes of excitons generated in N3 domain and improved exciton dissociation and change transport. PM6:N3:PY-P2 organic photovoltaic cells at 1 cm 2 and the corresponding mini-module achieved high efficiency of 15.18% and 14.7%, respectively. PY-P2 effectively improves OPV thermal stability under 1000 h heating. ga1 Highlights: Effect of the second polymeric acceptor, PY-P2, introduced in PM6:N3 blend. Improved charge generation and transport by pseudo-charge transfer state in BHJ film. High efficiency 1 cm 2 OPV fabricated by a blade-coating. High-performance OPV mini-module with 14.7% PCE. Enhanced thermal stability with the addition of PY-P2 polymeric acceptor.